PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV MI AL-MUHSININ RIMBA MELINTANG - Fathkul Jannah; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The causes its low achievement of civic in fourth grade MI Al-Muhsinin Rimba Melintang was the teacher just explain the subject, give the example and give the exercise in front of the class. that's why the author need to did the research by implicated model of learning type Numbered Head Together (NHT). This model can increase student's activity, teacher's activity and the achievement of civic. the main of implicated of this model was to increase the achievement of civic in fourth grade MI Al-Muhsinin Rimba Melintang. This research used classroom action research.. The result of analysis teacher's activity shown that increase in every siclus. teacher's activity in the first meeting is 58,33% increased to be 66,67% in the second meeting. And then increased in the third meeting to be 78,57% and increased to be 83,33 in the fourth meeting. And then increase of the learning achievement from basic average to test I is 72,25 with percentage 6,01%. And from test I to test II Increased to be 75,5 with percentage 10,78%. So, there was increase of learning achievement in every siclus.Key Word: Learning Model Cooperative Type Numbered Head Together, Student’s Achievement